The influence of etiological factors on immunoreactivity in patients with community-acquired pneumonia - A. V. Rvacheva; A. A. Pustovalov; K. A. Zykov (Клиническая практика, 2018)
The aim of this study was to uncover the characteristics of immunoreactivity in patients with community-acquired pneumonia, depending on the pathogen. The inflammatory process caused by various pathogens, has its own characteristics and affects the course of the disease. The study of the mechanisms of these complex interactions can improve the understanding of the processes occurring in community-acquired pneumonia, and, therefore, develop individual approaches to the therapy depending on the etiological factor.